39 Allelic expression imbalance at interleukin 18 and chemokine cxcl 16 in patients with acute coronary syndromes. (7th October 2015) - Gahan, JM; Byrne, MM; Connolly, E; Gray, SG; Anney, RJL; Murphy, RT; Ryan, AW
Abstract : Background: Many disease-associated genetic variants do not affect protein structure but may influence levels of gene expression through differential binding of transcription factors. This leads to allelic expression imbalance (AEI), where one chromosome in a heterozygote produces higher levels of messenger RNA than its paired chromosome. CXCL-16 is a chemokine which has been implicated in atherosclerosis and in particular in the pathophysiology of acute plaque rupture. It is induced by interferon gamma, which is in turn induced by interleukin-18 (IL18). 48 patients presenting to St James's Hospital with Acute Coronary Syndromes (ACS) were screened for heterozygosity at CXCL16rs2277680 and IL18rs360717, and analysed for AEI using Taqman ™ technology. Sulforaphane (1-isothiocyanato-4-(mathylsuffinyl)-butane) is thought to be principally responsible for the health benefits associated with cruciferous vegetables due to its activity as an anti-oxidant. Results: Five of 22 CXCL16rs2277680 heterozygous patients exhibited AEI, while all 8 IL18rs360717 heterozygotes exhibited imbalance. In 5 patients of 22 CXCL16rs2277680 heterozygous patients exhibited AEI, while all eight IL18rs360717 heterozygote patients exhibited imbalance. In addition to clinical samples, we analysed immortalised heterozygous lymphoblastoid cell lines for AEI at the same genes. 8 of 9 IL18rs360717 heterozygous cell lines exhibited AEI. None of 10 analysed CXCL16rs2277680 heterozygous cell lines initially showed AEI. However, stimulation by TNFalpha (100 ng/Âµl) induced AEI in 5 of these. Among the remainder, treatment with sulphoraphane, a histone deacetylase inhibitor prominent in green vegetables, induced AEI in 2 cell lines. Conclusions: These data show that AEI can be observed in ACS patients and can be enhanced in cell lines by stimulation with TNFalpha, thus reproducing the pro-inflammatory environment of ACS. This effect can be further modulated by treatment with sulphoraphane, suggesting an epigenetic effect which warrants further investigation.